An Update on National Consensus Practice Guidelines for the Treatment of Hepatitis C & Literature Review in Epidemiology of Hepatitis C in Pakistan - 2022 - Sibt ul Hasnain Syed; Muhammad Umar; Hamama tul Bushra Khaar; Tayyab Saeed Akhter; Tassawar Hussain; Amjad Salamat; Syed Irfan Ahmad; Rai Muhammad Asghar; Muhammad Khurram; Anwar A. Khan; Fazl-e-Hadi; Aftab Mohsin; et al. (Journal of Rawalpindi Medical College)
Hepatitis C is a global health problem affecting around 58 million people worldwide and killing almost 0.29 million in on one year [1]. The world has united to fight against this lethal disease in 2016 with a moto to eliminate hepatitis by 2030. To achieve this goal WHO’s World Health Assembly has set some targets and individual countries have developed their own strategies to achieve those targets [2].  Pakistan has the 2nd highest prevalence of hepatitis C in the world with 5.8% viremia positive patients [3]. Pakistan is amongst the few countries that have been assisted by the Center for Disease Control and Prevention(CDC) to prevent and control Hepatitis[4].